Knowledge strategy as an approach for competitive advantage for technology-based companies - Mhd. Sarif, Suhaimi; Ismail, Yusof (Malaysian Institute of Management, 2013)
The aim of this paper is to examine the role of knowledge strategy in creating and sustaining competitive advantage for technology-based companies. Technology-based companies continue to acquire knowledge in order to explore and exploit technology-based products and services. The study uses the qualitative method, specifically, separate personal interviews with 10 managers of technology-based companies located in Technology Park Malaysia and Cyberjaya. These informants argue that a knowledge strategy approach provides them continuous ideas to explore and exploit indigenous technology-based products and services. They also think that the approach will provide the same result to non-indigenous products and services. The results, at best, can be considered a case study of selected firms at the locations under study. As in any industry, companies in the technology-based industry must possess the ability to explore and exploit technology-based products and services in order to survive and remain competitive. There are reciprocal expectations from society and industry by offering the technology-based industry competent knowledge workers and strategists, society expects the technology-based industry to offer attractive rewards. Knowledge strategy enables technology-based companies to explore and exploit technology-based products and services.